2019
DOI: 10.3389/fphar.2019.00511
|View full text |Cite|
|
Sign up to set email alerts
|

Abscopal Effects in Radio-Immunotherapy—Response Analysis of Metastatic Cancer Patients With Progressive Disease Under Anti-PD-1 Immune Checkpoint Inhibition

Abstract: Immune checkpoint inhibition (ICI) targeting the programmed death receptor 1 (PD-1) has shown promising results in the fight against cancer. Systemic anti-tumor reactions due to radiation therapy (RT) can lead to regression of non-irradiated lesions (NiLs), termed “abscopal effect” (AbE). Combination of both treatments can enhance this effect. The aim of this study was to evaluate AbEs during anti-PD-1 therapy and irradiation. We screened 168 patients receiving pembrolizumab or nivolumab at our center. Inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 44 publications
(55 reference statements)
0
55
0
Order By: Relevance
“…It is estimated that more than 50% of patients with solid tumours receive radiotherapy (RT), which has an advantage over chemotherapy in that it limits systemic toxicity. 85 In combination with immune checkpoint inhibitors, RT normalizes the tumour vascular system, enhances the expression of leukocyte adhesion molecules on endothelial cells, and results in secretion of CD8 + T-attracting chemokines. RT triggers immunogenic cell death by inducing cell surface exposure of calreticulin (CALR) and ATP secretion via autophagy and IFN-I-induced upregulation of MHC-I, HSP70 exposure, TLR3 signal, high-mobility group box 1 (HMGB1) release and IL-1β release.…”
Section: Combinations With Other Therapiesmentioning
confidence: 99%
“…It is estimated that more than 50% of patients with solid tumours receive radiotherapy (RT), which has an advantage over chemotherapy in that it limits systemic toxicity. 85 In combination with immune checkpoint inhibitors, RT normalizes the tumour vascular system, enhances the expression of leukocyte adhesion molecules on endothelial cells, and results in secretion of CD8 + T-attracting chemokines. RT triggers immunogenic cell death by inducing cell surface exposure of calreticulin (CALR) and ATP secretion via autophagy and IFN-I-induced upregulation of MHC-I, HSP70 exposure, TLR3 signal, high-mobility group box 1 (HMGB1) release and IL-1β release.…”
Section: Combinations With Other Therapiesmentioning
confidence: 99%
“…In addition to the capability of maximizing the volume reduction of symptomatic lesions, local treatments can also boost the immunogenicity of the tumor, by increasing the release of TAA, and thus stimulating a systemic response against distant nodules. This phenomenon, known as the “abscopal” effect, was described for the first time in association with radiation therapy [ 56 ], but the same mechanism is valid also for ECT. In fact, both radiotherapy and ECT are able to induce ICD and thus to boost the immune response against cancer.…”
Section: Resultsmentioning
confidence: 95%
“…1 Although the precise mechanism of the abscopal effect remains unclear, an increasing number of reports in the current immune checkpoint inhibitor era support the hypothesis that activation of the immune system as well as modulation of the tumor microenvironment by radiation and immune checkpoint inhibitor therapies definitely play important roles in the abscopal effect. 2 In this issue of IJU Case Reports, Nakajima et al reported a possible abscopal effect of radiation therapy after discontinuation of nivolumab in mRCC. 3 In this report, a patient with mRCC of International mRCC Database Consortium intermediate risk underwent targeted therapy using pazopanib, axitinib, and everolimus.…”
Section: Editorial Comment Editorial Comment From Dr Yuasa To Possiblmentioning
confidence: 98%